GEOCHRONOLOGY OF NEOGENE-QUATERNARY VOLCANISM OF THE GEGHAMA HIGHLAND (LESSER CAUCASUS, ARMENIA) - Arutyunyan E.V.; Lebedev V.A.; Chernyshev I.V.; Sagatelyan A.K. (My University, 2007)
This work continues the systemic isotopic–geochronological studies of Late Cenozoic volcanism in the Lesser Caucasus [1–5] undertaken to elaborate the general regional scale of magmatic activity in this region during the Neogene–Quaternary and to establish neovolcanic centers potentially hazardous in terms of possible catastrophic eruptions. The young magmatism in the Caucasian segment of the Alpine belt that developed in the course of collision between the Eurasian and Arabian lithospheric plates is genetically related to the activity of the mantle “hot field”, which determined the prevalence of basic rocks among volcanics. The most intense pulses of volcanic activity during the Neogene–Quaternary are recorded in the Lesser Caucasus and eastern Anatolia, while young igneous rocks are distributed only in small areas of the Greater Caucasus.
Keywords: Quaternary; Neogene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene; Кайнозой::Неоген